Pengaruh Kualitas Pelayanan dan Kepuasan Terhadap Minat Kunjungan di Puskesmas Sangkapura (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
Increasing the quality of service will impact satisfaction and attract Interest in visits to public health services. This study aims to analyze the effect of service quality and satisfaction on Interest visits to Sangkapura public health services. The research method uses a cross-sectional study design. This research was conducted at the Sangkapura Public Health Center outpatient polyclinic starting in June-October 2022. There were 250 samples in the study with inclusion criteria, new patients, general patients, and patients who were at the Sangkapura Health Center and received services—sampling with a purposive sampling technique. The data analysis methods used were univariate analysis, chi-square, and multiple logistic regression tests. The results of the chi-square test showed that service quality (p-value 0.039